2019
DOI: 10.3390/su11092655
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mechanical Property Variation of As-Processed Bast Fibers

Abstract: Hemp, flax, and kenaf are bast fibers with promising material characteristics to sustainably displace synthetic fibers used in composites; however, their use in composite applications is hindered by high material property variability. More widespread adoption and application, as well as improved quality methods, of fibers is contingent on the reduction of this variability. Efforts made herein to assess variability in as-processed fibers and methods were found to identify key sources of variability by investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Moreover, major crop accidents (pronounced hydric stress or lodging phenomena, for instance) may have resulted in fibres with weak properties; these two extremes nevertheless remain rare. Beyond the agronomic conditions, the intrinsic structural parameters of the fibres, such as the MFA, fibre composition, diameter and presence of defects, have a substantial impact on the mechanical properties of plant fibres [161]. Aslan et al [38] referred to the distribution of defects along flax elementary fibres to explain the scattering of data and shape of the stress-strain curves.…”
Section: Mechanical Testing Of Flax Fibresmentioning
confidence: 99%
“…Moreover, major crop accidents (pronounced hydric stress or lodging phenomena, for instance) may have resulted in fibres with weak properties; these two extremes nevertheless remain rare. Beyond the agronomic conditions, the intrinsic structural parameters of the fibres, such as the MFA, fibre composition, diameter and presence of defects, have a substantial impact on the mechanical properties of plant fibres [161]. Aslan et al [38] referred to the distribution of defects along flax elementary fibres to explain the scattering of data and shape of the stress-strain curves.…”
Section: Mechanical Testing Of Flax Fibresmentioning
confidence: 99%
“…Several are the natural materials and vegetable waste that may have relevant mechanical properties, mainly in its fiber format, and which have been characterized by various authors in recent years. As observed in Table 1, showing a range of minimum and maximum values of mechanical data analyzed by different authors, the mechanical behavior of the different natural fibers is highly variable, significantly affecting the process of obtaining and pretreatment [2,3], in addition to the variability of the species itself, the specific conditions of the environment in which each plant develops, the moisture content or the uncertainty associated with the cross-section measurement process for calculating the stress-strain curve [4,5]. Classifying these fibers by their specific tensile strength, and except for the high performance of kenaf, the fibers obtained from the Canary banana are among the highest performance fibers, surpassing sisal, hemp or jute, and presenting a close behavior to the widely spread glass fibers, which places it in an advantageous position for use as a reinforcing material in plastic composites.…”
Section: Introductionmentioning
confidence: 99%
“…Various other authors have reported that using natural fibers leads to inconsistent composite properties. 19 Paper, fabrics, or mats can be prepared from natural fibers to reduce property variability. Paper preparation is especially beneficial in the case of various waste products that contain natural fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that viscosity was reduced by increasing the AESO temperature to 50°C, and composites with fiber loadings up to 70 wt% were produced. Various other authors have reported that using natural fibers leads to inconsistent composite properties 19 . Paper, fabrics, or mats can be prepared from natural fibers to reduce property variability.…”
Section: Introductionmentioning
confidence: 99%